Chronic Subdural Haematoma: Clinical Presentation and Surgical Outcome (Medical Forum Monthly, 2024)
Objective: Chronic subdural hematoma having diversity of clinical features, poor index of suspicion and non availability of CT scan is still diagnosed very late in AJK.The objective of study was to find out the clinical status at the time of admission and outcome of surgery in these patients managed in our hospital.Study Design: Descriptive Study.Place and Duration of Study: This study was conducted at the DHQ Hospital Mirpur AJK from March 2006 to April 2010.Materials and Methods: A total number of 47 patients with chronic subdural hematoma of all age groups were operated at DHQ hospital Mirpur in this period. Clinical presentation of the patients at the time of admission was recorded. Patients were followed for a period of 2-3 months after surgeryResults: Forty seven patients were studied. Among them 40(85%) were male and 7(15%) were female. The age range was 2 months to 100 years with average age 52.5 years. Thirty one (66%) had positive history of head trauma whereas 16 patients (34%) did not remember any injury. Thirty one (66%) had headache, 35(74.5%) had hemiparesis, 19(40.4%) had behavioral changes and urinary incontinence. Six patients (12.8%) were having GCS 3 with reactive pupils. One (2.1%) patient came with decreased vision. CT scan showed unilateral hematoma in 37 (78.7%) and bilateral in 10 (21.3%) patients. Twenty five (53%) patients had hematoma on left side, 12(25.5%) had hematoma on right side and 10(21.3%) had bilateral hematoma. Thirty four (72.3%) had good recovery. Four (8.5%) could not survive.Conclusion: Chronic subdural hematoma due to diversity of symptoms, poor index of suspicion, and non availability of CT scan is still diagnosed very late in AJK.Elderly patients with diversity of confusing neurological symptoms need to be kept under high index of suspicion for diagnosis of chronic subdural hematoma. Drainage of Chronic subdural hematoma with two burr holes and placement of subdural drain offered excellent